Factors influencing distribution and local coexistence of diploids and tetraploids of Vicia cracca: inferences from a common garden experiment - Eliášová, Anežka; Münzbergová, Zuzana (Journal of plant research, 2017)
Vicia cracca diploids and autotetraploids are highly parapatric in Europe; tetraploids reside in western and northern part, whereas diploids occupy much drier south-eastern part. They meet together in a Central European contact zone. This distribution pattern raised questions about a transformative effect of polyploidization on plant performance and environmental tolerances. We investigated plant survival, growth, and seed production in two water regimes in a common garden experiment using seeds collected from five localities in the Central European contact zone where diploids and tetraploids occur in sympatry. Obtained data imply that tetraploids of V. cracca are not generally superior in performance to diploids. Significantly larger seeds from tetraploid mother plants collected in the field were not correlated with greater stature of the seedlings. Nonetheless, tetraploids might have a potential to out-compete diploids in the long run due to the tetraploids' ability of greater growth which manifested in the second year of cultivation. Considering the response of diploids and tetraploids to water supply, drought stressed tetraploids but not diploids produced a higher proportion of aborted seeds than watered ones, which implies that tetraploids are more drought susceptible than diploids. On the other hand, decreased plant height in drought stresses tetraploids, which simultaneously increased total seed production, may suggest that tetraploids have a greater ability to avoid local extinction under unfavourable conditions by enhancing biomass allocation into production of seeds at the cost of lower growth. The significant interaction between ploidy level and locality in several traits suggests possible polyfyletic origin of tetraploids and the necessity to clarify the history of the tetraploids in Europe.
Keywords: Ploidies; Gardens; Europe; tetraploidie; Biomass; Seeds; semena rostlinná; diploidie; Evropa; ploidie; Tetraploidy; vikev; sympatrie; Sympatry; Diploidy; Vicia; semenáček; Seedlings; biomasa; zahrady